Stability of Human Gallbladder Bile: Effect of Freezing - Paul Janowitz; Richard Mason; Wolfgang Kratzer (Canadian Journal of Gastroenterology)
In the present study, the stability of the most essential biliary parameters of human gallbladder bile at -18°C was examined over several months. In 12 patients with gallstone disease (10 female, two male; 52.1±13.3 years of age), bile was obtained through fine needle puncture of the gallbladder under local anesthetic. The concentrations of total lipids, cholesterol, phospholipids and bile acids, and the cholesterol saturation index and crystal appearance time were determined before and after freezing over a mean period of 4.38±2.9 months. Gallbladder bile obtained by fine needle puncture has proved to be of excellent quality. The total lipid concentration was unchanged before (8.30±4.16 g/dL) and after freezing (9.16±4.54 g/dL, P=0.6027). The biliary cholesterol, phospholipids and bile acid concentrations, and cholesterol saturation index showed no statistically significant differences before and after freezing. A significant difference arises in the context of subdivision of the group to the nucleation time. Before freezing, most patients had a nucleation time between five and eight days, which shortened to between one and four days after thawing (P=0.0100). The authors conclude that, with the exception of the nucleation time, human gallbladder bile can be stored at -18°C for four months with stability of major lipid components.